History of Women in the Pre-Independence Era - Lestari, Annisa Fitri (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
Women as citizens of society, have the full right to think about the problems of society, seek solutions to the problems faced and try to build the community in accordance with their desires and beliefs, The struggle of women in 1928 began with the Indonesian Women's Congress which was first held in Yogyakarta on December 22, 1928. This research method uses the document study method and with the results of Women's organizations in the pre- independence era starting with the pppi. And there were many female figures who fought for women's independence.